Electric field modulation of 2D perovskite excitonics - Zhang, Qiannan (2022)
Multiquantum-well (MQW) perovskite is one of the forerunners in high-efficiency perovskite LED (PeLEDs) research. Despite the rapid inroads, PeLEDs suffer from the pertinent issue of efficiency decrease with increasing brightness, commonly known as "efficiency roll-off". The underlying mechanisms are presently an open question. Herein, we explicate the E-field effects on the exciton states in the archetypal MQW perovskite (C6H5C2H4NH3)2PbI4, or PEPI, in a device-like architecture using field-assisted transient spectroscopy and theoretical modeling. The applied E-field results in a complex interplay of spectral blueshifts and enhancement/quenching of the different exciton modes. The former originates from the DC Stark shift, while the latter is attributed to the E-field modulation of the transfer rates between bright/dark exciton modes. Importantly, our findings uncover crucial insights into the photophysical processes under E-field modulation contributing to efficiency roll-off in MQW PeLEDs. Electrical modulation of exciton properties presents exciting possibilities for signal processing devices.